Juz Amma Memorization’s Role In Strengthening The Character Of Discipline And Responsibility Of Students In Primary School - Endrik Mas Yulaidi; Wildan Irwahyudi; Ahmad Khoiri; Ade Eka Anggraini; Azizatus Zahro' (Published by the Islamic Religious Education Study Program Faculty of Tarbiyah and Teacher Training Kiai Haji Achmad Siddiq University, Jember, East Java, Indonesia, 2022)
The current educational Program is directed to the implementation and strengthening of character education in schools. Character of discipline and responsibility is considered as the right solution to solve the problems of the Indonesian nation, especially in Islamic Religious Education as the basis for creating the character of discipline and responsibility. The purpose of this study was to determine the impact of memorizing Juz Amma during the Covid - 19 pandemic on post-Covid-19 on the character of discipline and responsibility. Data collection techniques used in this study were interviews and documentation studies. This research was conducted in the Laboratory of Elementary School University of Malang, Blitar. The results of this study indicate that Juz Amma's online learning research has produced new innovations for Islamic religious education teachers that can be done remotely with the help of modern technology. (1) The implementation of hafal juz'amma was carried out every morning with different teaching methods used every day, and led by their respective classroom teachers. (2) Implementation of memorizing juz'amma in fostering the character of discipline, namely by requiring students to arrive on time, follow the activities in an orderly and neat manner, require students to obey the rules. (3) The implementation of memorizing juz'amma in fostering the character of responsibility is by giving memorized letters and obliging students to bring juz'ama or al-qur'an every day. However, when memorized Juz Amma online has some obstacles in the learning process such as practical-based learning materials, the practice is not effective if done online so it needs repetition when learning is done face to face (New Normal) in addition to other obstacles, such as children who have no control when playing mobile phones, so he could not concentrate on the lesson, so the teacher visited the student's home once a week as a function of control over learners. Studying during the post - covid-19 period cannot be said to have recovered from the pandemic, students who learn the habit of using technology such as mobile phones. That's when the teacher's innovations in learning are used so that students return to normal learning as before the pandemic Keywords: Islamic Religion Education, Juz Amma, Learning